Direct synthesis of isobutyraldehyde from methanol and ethanol on Cu–Mg/Ti-SBA-15 catalysts: the role of Ti. (8th August 2017) - Zhang, Junfeng; Zhang, Meng; Wang, Xiaoxing; Zhang, Qingde; Song, Faen; Tan, Yisheng; Han, Yizhuo
Abstract : An increase in the Ti content significantly improves catalyst durability due to its effect on Cu dispersion and the basicity of the catalyst. Abstract : Herein, Cu–Mg/Ti-SBA-15 catalysts were prepared through the modification of Cu and Mg to mesoporous Ti-SBA-15 zeolites with different Ti/Si ratios and used for the synthesis of isobutyraldehyde (IBA) from methanol and ethanol. The catalysts were characterized via various techniques including XRF, XRD, TEM, N2 sorption, CO2 -TPD, FT-IR, and XPS. With an increase in Ti content, CuO was well dispersed accordingly, and the amounts and strength of the basic sites were reduced. However, an excess introduction of Ti led to the accumulation of single TiO2 crystals, inducing a decrease in the surface area and a deviation from the regular pattern such that the binding energies of Cu 2p, Mg 2p, and Si 2p shifted to lower values. This precisely affected the catalytic behaviors of the prepared catalysts synergistically. The catalyst stability was improved with the increasing Ti content accordingly, and over the catalyst with a Ti/Si ratio = 4/15, the IBA selectivity, after 24 h reaction, could still reach 25%, which was the best durability ever reported for IBA synthesis from methanol and ethanol. The catalytic performance test conducted using a regenerated catalyst and IR measurement of the spent catalyst indicated that carbon deposition on the catalyst surface could be depressed to some extent with the increasing Ti content.